Approaching Combined Rectal and Vaginal Prolapse - Wallace, Shannon; Gurland, Brooke (Clinics in Colon and Rectal Surgery, 2021)
Combined rectal prolapse and pelvic organ prolapse surgery provides significant quality-of-life benefits with improvements in bothersome symptoms of pain, bulge, constipation, urinary retention, as well as bowel and bladder incontinence. Robotic surgery is the ideal tool for a combined surgical repair. It allows enhanced suturing in the deep pelvis, three-dimensional (3D) visualization of the presacral space and easy mobilization of the rectum and dissection of the vagina. Combined procedures can be offered to patients with the advantages of a single operation and concurrent recovery period without increasing complications. In this article, we highlight our approach to combined prolapse repair.
Keywords: robotic rectopexy and sacrocolpopexy; rectal prolapsed; pelvic organ prolapsed; ventral rectopexy; sacrocolpopexy; multidisciplinary pelvic floor approach